The Impact of Computer Assisted Language Learning (CALL) Use of English Vocabulary Enhancement - Yuri Lolita; Endry Boeriswati; Ninuk Lustyantie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims at improving students’ comprehension on English vocabulary using computer and finding out the effectiveness, efficiency and the attractiveness of Computer Assisted Language Learning (CALL) in English learning. It was carried out at SMP Sunan Giri Gresik by using proactive action research method and intervention action model. The participants belonged to 3 different class groups. Thirty of them were from 7th grade (Amanah class) and thirty-two of them from (Hidayah class). The other 30 participants from (Inayah class). The data were collected and analyzed by using mixed method approach. Instruments used for collecting data in this study are questionnaires, documents, observation check list, interview, and achievement tests. The results showed that the treatments give affect positively for students especially treatment on cycle 2. It also can be seen by the students’ involvement actively during learning process. Computer assisted learning especially using software gave students chance to explore their English skill especially the vocabulary through interacting directly with computer by doing exercises given individually in pair or group. From the explanation above it can be concluded that English learning in junior high school can be improved with the help of computer assistance in this matter called Computer-Assisted Language Learning (CALL) mainly to improve English vocabulary. Keywords: Computer-assisted language learning (CALL), English vocabulary, Students’ comprehension